Pengenalan Teknologi Virtual Reality BOX dalam Pembelajaran Komputer - Abdul Karim; Dwika Assrani; Guidio Leonarde Ginting (Forum Kerjasama Pendidikan Tinggi, 2024)
In today's digital age, the utilisation of advanced technology in learning is increasingly important to increase effectiveness and student engagement. This article aims to explore the use of Virtual Reality BOX technology in computer learning, focusing on how this technology can improve students' understanding and skills in computers. The main problem encountered is the limitation of traditional learning methods that often cannot provide adequate practical experience in the context of computers. To address this issue, the method used involves the introduction and integration of Virtual Reality BOX as an aid in the teaching-learning process. This technology enables interactive simulations and virtual environments that can enrich students' learning experience. Interim results from the implementation of this technology show an increase in students' motivation and understanding of the computer concepts being taught. The implementation of Virtual Reality BOX has shown significant potential in making computer learning more interesting and effective.